Effects of N-starvation and C-source on Bradyrhizobium japonicum exopolysaccharide production and composition, and bacterial infectivity to soybean roots - Quelas, Juan Ignacio (2006)
The exopolysaccharide (EPS) is an extracellular molecule that in Bradyrhizobium japonicum affects bacterial efficiency to nodulate soybean. Culture conditions such as N availability, type of C-source, or culture age can modify the amount and composition of EPS. To better understand the relationship among these conditions for EPS production, we analyzed their influence on EPS in B. japonicum USDA 110 and its derived mutant ΔP22. This mutant has a deletion including the 3′ region of exoP, exoT, and the 5′ region of exoB, and produces a shorter EPS devoid of galactose. The studies were carried out in minimal media with the N-source at starving or sufficient levels, and mannitol or malate as the only C-source. Under N-starvation there was a net EPS accumulation, the levels being similar in the wild type and the mutant with malate as the C-source. By contrast, the amount of EPS diminished in N-sufficient conditions, being poyhydroxybutyrate accumulated with culture age. Hexoses composition was the same in both N-situations, either with mannitol or malate as the only C-source, in contrast to previous observations made with different strains. This result suggests that the change in EPS composition in response to the environment is not general in B. japonicum. The wild type EPS composition was 1 glucose:0.5 galactose:0.5 galacturonic acid:0.17 mannose. In ΔP22 the EPS had no galactose but had galacturonic acid, thus indicating that it was not produced from oxidation of UDP-galactose. Infectivity was lower in ΔP22 than in USDA 110. When the mutant infectivity was compared between N-starved or N-sufficient cultures, the N-starved were not less infective, despite the fact that the amounts of altered EPS produced by this mutant under N-starvation were higher than in N-sufficiency. Since this altered EPS does not bind soybean lectin, the interaction of EPS with this protein was not involved in increasing ΔP22 infectivity under N-starvation.